Kolaborasi Pemangku Kepentingan dan Warga dalam Upaya Pencegahan Tindakan Korupsi di Bandar Lampung - Juan Felix Emanuel (Pemuliaan Keadilan, 2024)
Corruption is a serious challenge faced by Indonesia especially Bandar Lampung city, hampering development, undermining public institutions, and reducing public trust in the government. Efforts to prevent and address corruption are not only the responsibility of state institutions, but also require the active participation of various stakeholders, including civil society, the private sector, and the media. This article highlights the importance of collaboration between stakeholders in preventing and addressing corruption. By analyzing various collaborative initiatives that have been successfully implemented in several regions in Indonesia, this article shows that citizen involvement can strengthen the effectiveness of anti-corruption policies, increase transparency, and encourage public accountability. The role of citizens is crucial as social monitors who participate in monitoring the implementation of anti-corruption policies and programs implemented by the government. The success of efforts to eradicate corruption is also determined by the synergy between related institutions and the active involvement of the community. With organized and mutually supportive cooperation, it is hoped that efforts to prevent and handle corruption can be more effective and sustainable, thus strengthening clean and accountable governance in Bandar Lampung City.